'Otherness as a condition of citizenship': alterity, extimacy and citizenship after orientalism. Issue 3 (3rd April 2023) - A. Morrison, Ian
ABSTRACT: From the genealogies of citizenship in Being Political to his more recent explorations of performance and performativity, Engin Isin's attempts to think citizenship after orientalism have been explicitly guided by a 'focus on otherness as a condition of citizenship' (2002, 3). Both within and beyond the field of citizenship studies, Isin's call to investigate citizenship as alterity has contributed to a radical rethinking of the nature of citizenship, political subjectivity, collective identity, and the relation of self to other. It is the meaning of a 'focus on otherness as a condition of citizenship' that is addressed in this article. This is undertaken, first, by examining the place of otherness within Isin's investigations of citizenship. Second, it is argued that addressing otherness in terms of extimacy, a term which designates both the presence of exteriority in the deepest interiority (intimacy) of the subject, and the 'resultant nondistinction and identity of the exterior and the intimate or most interior' (Pavón-Cuéllar 2014, 661), allows us to recognize additional ways in which otherness serves as a condition of citizenship, and, thereby, to further pursue Isin's aim of understanding the relation of citizenship and otherness beyond logics of exclusion and enclosure. Approaching otherness as a condition of citizenship in terms of extimacy reveals the very scenes in which the categories of citizenship and its others are asserted, reproduced and/or overturned as implicated in and structured by structures of fantasy and desire.